Spousal communication on family planning and perceived social support for contraceptive practices in a sample of Malaysian women - Najafi Sharjabad, Fatemeh; Abdul Rahman, Hejar; Juni, Muhammad Hanafiah; Syed Yahya, Sharifah Zainiyah (Isfahan University of Medical Sciences, 2014)
Background: In Malaysia, contraceptive prevalence rate (CPR) during past three decades has been steady, with only 34% of women practicing modern contraception. The aim of this study was to determine the factors associated with modern contraceptive practices with a focus on spousal communication and perceived social support among married women working in the university.